The hybrid church in the city : third space thinking - Baker, Christopher Richard, 1961- (Ashgate, 2007)
This book argues that theology and the church need to engage more seriously with post-modern reality and thought if points of connection are going to be created. Drawing on case studies from Europe and the USA, this book examines examples of Third Space methodologies to ask questions about hybrid identities and methods churches might adopt to effectively connect with post-modern cities and civil society.